Victimization of foreign domestic helpers in Hong Kong. Issue 1 (3rd May 2016) - Wong, Hoi Kam Quinnci; Chan, Elana; Chan, Tak Ming Charles; Li, Yung; Wan, Ming Ki Henry
Abstract : Purpose: This paper aims to examine the forms and experiences of victimization of foreign domestic helpers (FDHs) in Hong Kong, the effects of victimization on FDHs and FDHs' coping strategies. Design/methodology/approach: The main findings are based on semi-structured interviews with a sample of 12 FDHs in Hong Kong. Findings: The findings uncovered a continuum of violence ranging from relatively mundane abuses on an everyday basis to acute events at the time of termination. Some respondents also experienced secondary victimization from police and/or pending criminal justice proceedings after contract termination. Research limitations/implications: Victimization exerted significant adverse physical and psychological effects on FDHs in our study. Nevertheless, contrary to common assumptions about FDHs as passive victims, our findings suggest that some FDHs experienced a degree of empowerment, as they found ways to cope with their difficulties by individualized and social strategies depending on the degree of victimization and the resources available. Originality/value: The findings suggest there is an urgent need to review the existing laws and policies that, at best, are ineffective and, at worst, create far more problems than they solve.